Research and Development in Accounting Science with a Qualitative Approach Methodology - Susilo, Tri Achmad Budi; Setiawan, Ainur Rahim; Sinaga, S. Bungaran; Irianti, Rosi; Moch. Dicky Riza; Ira Puspitasari (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2024)
The purpose of writing this article is to describe and deepen the study of qualitative interpretive accounting with various schools of thought, describe the advantages and limitations of interpretive accounting research and show the low level of qualitative interpretive research compared to quantitative research in Indonesia. The method used in this research is to use a qualitative approach with secondary data methods, namely through literature studies obtained from journals or articles that support. Positive/qualitative and interpretative/qualitative research models are complementary research models, there is no dichotomy between the two. The relationship between accounting and sociology and the continuous development of society is strong enough to underline the need to develop interpretative/qualitative research in accounting. The identification of research methods using solipsism, phenomenology, hermeneutics, ethnographic methodology, and symbolic interactionism is based on the ontological and epistemological assumptions of the research, for researchers to determine the most suitable method. So that qualitative research does not become a complement in the development of accounting science, it becomes a paradigm choice in developing research.